Enhancement Strategy of Prospective Students’s Interest in Zakat and Waqf Management Program - Rodame Monitorir Napitupulu; Sarmiana Batubara; Fahrina Putri Sapna (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2021)
Abstract, The program of Zakat and Waqf Management at the Faculty of Islamic Economics and Business IAIN Padangsidimpuan experienced a decline in the number of students from 2018 to 2020. As a study program with a field of science that is currently trending nationally and globally, there should be an increasing number of enthusiasts, but on the contrary actually decreased. Therefore, the purpose of this study was to analyze the strategy of increasing the interest of prospective students of the Zakat and Waqf Management Study Program. This study uses a descriptive qualitative approach where the number of informants is 333 people, namely senior high school students and students from Islamic boarding schools in Padangsidimpuan City, South Tapanuli Regency and other surrounding cities/regencies. The results of the study indicate that there is some academic and non-academic information that must be added to various existing promotional media. Promotional media that must be maintained are direct selling (official websites), social media (Facebook, Instagram and Youtube, advertisements (brochures), personal selling (promotion teams to schools).